PENGEMBANGAN E-LKPD BERBANTUAN MEDIA WORDWALL MENGGUNAKAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Alfigo, Rama; Hamimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the limited use of technology-assisted student worksheets (LKPD) in science and social studies (IPAS) learning in elementary schools. It aimed to develop an electronic LKPD (E-LKPD) supported by Wordwall media using the Problem Based Learning model for biodiversity material in fourth grade. The problem was identified through observations and needs analysis in several elementary schools, which showed that teachers rarely used technology-based LKPD in the learning process. As a result, students tended to be less active and less motivated during learning activities. This study used a Research and Development (R&D) approach with the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The data collected included validation and practicality data. Validation data were obtained through expert judgment involving material, language, and media experts, while practicality data were gathered through questionnaires from teachers and students regarding the use of the developed E-LKPD. The developed E-LKPD was then tested for practicality with teachers and students in several elementary schools. The results showed that the Wordwall-assisted E-LKPD obtained a practicality score of over 95%, categorized as highly practical. This indicates that the E-LKPD is easy to use, engaging, and supports students’ active participation in learning. In conclusion, the Wordwall-assisted E-LKPD developed using the Problem Based Learning model is feasible and practical for use in fourth-grade IPAS learning.